X-sat microsatellite space bus design and development - Arichandran, K. (2008)
A detailed structural and thermal analysis is a pre-requisite for ensuring satellite integrity, both during launch and orbit operation in space. A study has been made on structural/vibrational characteristics as well as the thermal behavior of NTU’s micro-satellite X-Sat and this is presented in this report. X-Sat (of nominal mass 100 Kg and volumetric dimensions of 60cm x 60cm x 80 cm) is a microsatellite being developed in NTU. The key development work on the satellite bus is being done completely in the University. The primary payload of the X-Sat is an imaging payload called the IRIS payload. This payload is not developed in NTU and is supplied from South Korea under a contract handled by DSO. Under this RGM, two major subsystems, namely the structural and thermal subsystems of the satellite bus have been analysed in order to arrive at a suitable design. The report is divided into two sections. Section A discusses the structural configuration requirements of X-Sat, the methodology of analysis and results obtained. Finite Element modeling and the analysis results are presented in detail. Also, the coupled load analysis of the X-Sat bus with the IRIS payload is discussed. Section B presents the thermal controls design, modeling and analysis results for the X-Sat configuration, the Thermal Balance Test (TBT) design and the necessary analysis. With some simplifications and assumptions, the thermal analysis has been done for several cases (worst/normal hot and cold cases). The results indicate that the temperature conditions for most of the sub-systems and payloads were within the allowable limits. However, at the qualification level, the temperature of some components like battery and OBC exceeds the corresponding temperature limits, which need further improvement. This has been addressed with local thermal control techniques. Current X-Sat configuration is evolving and there may be some variation whenever the flight model is determined. The analysis presented here would allow the tracking of the structural and thermal behavior and help in optimizing the behavior of the flight model.